Development and Validation of Enantiomeric Purity of Montelukast by SFC Method on Amylose Based Stationary Phase (JOURNAL OF ADVANCES IN CHEMISTRY, 2008)
A new Supercritical fluid liquid chromatographic (SFC) method has been developed in normal-phase conditions for the determination of enantiomeric purity of Montelukast sodium (S,E)-2-(1-((1-3-(2-(7-chloroquinolin-2-yl)vinyl)phenyl)-3-(2-(2-hydroxypropan-2-yl)phenyl)propylthio)ethyl) cyclopropyl) acetic acid (R-isomer) (Anti asthmatic drug) in bulk drugs and in dosage forms. The sample was screened on the analytical SFC to determine the best column for the separation. The screening conditions are Column: Chiralpak AS-H (250 mm x 4.6 mm, 5 Î¼m) column using a mobile phase system containing Supercritical fluid (Co2) and 2-Propanol in the ratio (85:15% v/v). The mobile-phase compositions and the differences in separation capability of the method is noted. The resolution between two enantiomers is found to be greater than 1.5. The SFC method for the separation of enantiomers of Montelukast is proved Accurate, Precise, Linear and robust. Relative standard deviation of retention times and peak areas were better than 0.2% and 0.4%, respectively, for precision.Â